We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
100
2
avatar+169 

Question Four:

 Mar 3, 2019
 #1
avatar+101856 
+1

Note that     f(3) + f(-3)   = f(3 - 3) =   f(0)

 

So

 

f(0) =  -12(0)^9 + 0   =   0

 

 

cool cool  cool

 Mar 3, 2019
 #2
avatar+169 
0

Thanks!

 Mar 3, 2019

9 Online Users